Drug Loading in Chitosan-Based Nanoparticles - Yedi Herdiana; Ellin Febrina; Siti Nurhasanah; Dolih Gozali; Khaled M. Elamin; Nasrul Wathoni (MDPI AG, 2024)
Chitosan nanoparticles (CSNPs) are promising vehicles for targeted and controlled drug release. Recognized for their biodegradability, biocompatibility, low toxicity, and ease of production, CSNPs represent an effective approach to drug delivery. Encapsulating drugs within nanoparticles (NPs) provides numerous benefits compared to free drugs, such as increased bioavailability, minimized toxic side effects, improved delivery, and the incorporation of additional features like controlled release, imaging agents, targeted delivery, and combination therapies with multiple drugs. Keys parameters in nanomedicines are drug loading content and drug loading efficiency. Most current NP systems struggle with low drug loading, presenting a significant challenge to the field. This review summarizes recent research on developing CSNPs with high drug loading capacity, focusing on various synthesis strategies. It examines CSNP systems using different materials and drugs, providing details on their synthesis methods, drug loadings, encapsulation efficiencies, release profiles, stability, and applications in drug delivery. Additionally, the review discusses factors affecting drug loading, providing valuable guidelines for future CSNPs' development.